CHLORINE STABLE ISOTOPE STUDIES OF OLD GROUNDWATER, SOUTHWESTERN GREAT ARTESIAN BASIN, AUSTRALIA - Zhang M.; Frape S.K.; Love A.J.; Herczeg A.L.; Lehmann B.E.; Purtschert R.; Beyerle U. (My University, 2007)
Stable Cl isotope ratios (37Cl/35Cl) were measured in groundwater samples from the southwestern flow system of the Great Artesian Basin, Australia to gain a better understanding of the Cl- sources and transport mechanisms. δ37Cl values range from 0‰ to -2.5‰ (SMOC), and are inversely correlated with Cl- concentration along the inferred flow direction. The Cl isotopic compositions, in conjunction with other geochemical parameters, suggest that Cl- in groundwaters is not derived from salt dissolution. Mixing of the recharge water with saline groundwater cannot explain the relationship between δ37Cl and Cl- concentration measured. Marine aerosols deposited via rainfall and subsequent evapotranspiration appear to be responsible for the Cl- concentrations observed in wells that are close to the recharge area, and in groundwaters sampled along the southern transect. δ37Cl values measured in the leachate of the Bulldog shale suggest that the aquitard is the subsurface source of Cl- for the majority of groundwater samples studied. Diffusion is likely the mechanism through which Cl- is transported from the pore water of the Bulldog shale to the aquifer. However, a more detailed study of the aquitard rocks is required to verify this hypothesis. © 2007 Elsevier Ltd. All rights reserved.